Damage Identification of Wind-Break Wall Structures based on the Further Updated Wavelet Packet Frequency Bands Energy Ratio Spectrum - Qian Xu (Shock and Vibration)
Damage will appear in the wind-break wall under the effects of many factors. The wind-break wall may be destroyed when the damage is accumulated to some extent, which may cause accidents. To identify damage within the wind-break wall structure, the Wavelet Packet frequency bands energy ratio spectrum analysis of the virtual impulse response function of responses to the wind-break wall was performed under the effects of excitation. Based on the damage sensitivity analysis of subfrequency bands, a further updated Wavelet Packet frequency bands energy ratio spectrum was proposed. To reflect the damage information sensitively, the feature bands, which were more sensitive to damage, were selected via the threshold value ε0. Then, the Wavelet Packet damage feature vector and damage identification index, which can reflect damage information of the wind-break walls sensitively, were proposed. A damage identification method for wind-break walls was proposed. To verify the validity of this damage identification method, the vibration tests on a pile plate wind-break wall were performed. Damage within the wall was identified via the method. The tests results show that the damage feature vector is a zero vector and the value of damage index is zero, when the wind-break wall is not damaged. The damage feature vector is a nonzero vector and the value of damage index is positive, when the wind-break wall is damaged. Thus, the damage state of the wind-break wall can be detected via the damage feature vector and damage index. With increase of damage accumulated within the wall, the damage intensity and the value of the damage index increase. The quantitative relationship between the damage index and damage intensity is established. The damage intensity can be calculated reversely, when the damage index is available. Thus, the damage intensity of the wind-break wall can be identified via the quantitative relationship between the damage index and damage intensity. In addition, the damage index value of the measuring point, which is much closer to the partial damage, is much larger. The damage index value of the point, which is located at the partial damage, is the largest. Thus, the damage location of the wind-break wall can be diagnosed via the characteristics of damage index for different measurement points. Thus, the damage state, damage location, and damage intensity of the wind-break wall can be identified via this damage identification method.